Income and wealth: Series X Income redistribution and the statistical foundations of economic policy (London Bowes and Bowes Publishers Ltd, 1964)
This book contains a selection of the papers presented at the Seventh General Conference of the International Association for Research in Income and wealth, held at Tutzing near Munich from 3rd to 10th August, 1961.
Includes index
osa; 22/6/17
Loans
Keywords: Clark, Colin; Stuvel, Geer; Income distribution - Congress